Vaccine hesitancy in migrant communities: a rapid review of latest evidence. (August 2021) - Tankwanchi, Akhenaten Siankam; Bowman, Brett; Garrison, Michelle; Larson, Heidi; Wiysonge, Charles Shey
Graphical abstract: Highlights: Clear evidence of vaccine hesitancy has been reported among migrant groups in multiple countries. Fear of measles vaccine harms intensified by anti-vaccination activism drives hesitancy among US-based Somali parents. Xenophobia diminishes trust in the host country health system and may exacerbate vaccine hesitancy among migrant populations. Abstract : By refusing or delaying vaccination, vaccine hesitant individuals and communities undermine the prevention, and ultimately, elimination of communicable diseases against which safe and effective vaccines are available. We reviewed recent evidence of vaccine hesitancy within migrant communities in the context of increased human mobility and widespread anti-immigrant sentiment and manifest xenophobia. Among many immigrant parents and families, vaccine hesitancy is largely associated with fears and misinformation about vaccine harms, limited knowledge of both preventable diseases and vaccines, distrust of host countries' health systems and their attendant intentions, language barriers, and perceived incompatibility between vaccine uptake and migrants' religion. Hesitancy toward measles, influenza, and human papillomavirus vaccines are most discernible, and main migrant populations involved include Somalis and Poles.